Changes in Physicochemical Indexes and Volatile Components during the Ripening Process of Gallnut Honey - Zao SHI; Xue YANG; Huiying LI; Shuxin ZHOU; Weizhong HU; Zhiqiang YI; Muying DU (Shipin gongye ke-ji)
This study aimed to investigate the changes in physicochemical indexes and volatile components of gallnut honey, a traditional Chinese herbal honey during its ripening process. A series of physicochemical indexes, including water content and amylase value, were measured at different stages of maturity. Additionally, the volatile components of gallnut honey were analyzed qualitatively and quantitatively using headspace solid-phase microextraction with gas chromatography-mass spectrometry (GC-MS), and the key aroma components were identified using relative odor activity value (ROAV). The results indicated that during the ripening process, the contents of protein, hydroxymethylfurfural, glucose, fructose, acidity and amylase value in gallnut honey increased, while the contents of water, electrical conductivity and sucrose decreased. The values of these indexes in mature gallnut honey were recorded as follows: 1.92±0.02 g/kg for protein, 0.67±0.03 mg/kg for hydroxymethylfurfural, 30.75±0.14 g/100 g for glucose, 35.90±1.08 g/100 g for fructose, 16.58±0.32 mL/kg for acidity, 20.59±1.25 mL/(g·h) for amylase value, 19.43±0.16 g/100 g for water content, 370.33±2.52 μs/cm for electrical conductivity and 2.62±0.12 g/100 g for sucrose. A total of 108 volatile components were identified across 11 categories, including acids, alcohols, aldehydes, and ketones, in gallnut honey at different maturation stages. The total amount of volatile components increased with longer brewing times, with aldehydes representing the highest proportion, ranging from 81.15% to 85.52%. Ketones were identified as the most diverse, comprising 24 species. Twelve key aroma components were selected from gallnut honey, 8 of which were common across all maturity stages: 2-methylbutyric acid, benzyl alcohol, benzaldehyde, phenylacetaldehyde, heptanal, nonanal, decanal and damastone. Notably, damastone, which imparted a fruity aroma, made the largest contribution to the overall fragrance of gallnut honey. The enhancement of floral and fruity aromas in gallnut honey was attributed to the interaction of these aroma components. This study provides theoretical guidance for the production and quality control of gallnut honey and offers research insights for the exploration of other distinctive traditional Chinese medicine honeys.